2021
DOI: 10.3389/fmicb.2021.636332
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Salmonella enterica Isolates From Retail Meat in Beijing, China

Abstract: Salmonella enterica remains one of the leading causes of foodborne bacterial disease. Retail meat is a major source of human salmonellosis. However, comparative genomic analyses of S. enterica isolates from retail meat from different sources in China are lacking. A total of 341 S. enterica strains were isolated from retail meat in sixteen districts of Beijing, China, at three different time points (January 1st, May 1st, and October 1st) in 2017. Comparative genomics was performed to investigate the genetic div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 79 publications
4
19
0
Order By: Relevance
“…Indiana, which was considered the most resistant serovar in this study, carries plasmid types IncX1_1, IncHI2_1, IncHI2A_1, and Col156_1; these plasmids have been associated with the acquisition of resistance to different classes of antimicrobials, including aminoglycosides, sulfonamides, tetracyclines, quinolones, polymyxins, and β-lactams ( 52 , 53 ). Furthermore, our findings demonstrated that the plasmid type IncX1, in addition to IncFII(S) and IncFIB(S), is the key carrier of antimicrobial resistance determinants in Salmonella , which is in agreement with previous findings from China and elsewhere ( 54 57 ). Hence, the presence of these plasmids in the studied isolates is of major concern and may mediate the horizontal transmission of antimicrobial resistance along the food chain.…”
Section: Discussionsupporting
confidence: 93%
“…Indiana, which was considered the most resistant serovar in this study, carries plasmid types IncX1_1, IncHI2_1, IncHI2A_1, and Col156_1; these plasmids have been associated with the acquisition of resistance to different classes of antimicrobials, including aminoglycosides, sulfonamides, tetracyclines, quinolones, polymyxins, and β-lactams ( 52 , 53 ). Furthermore, our findings demonstrated that the plasmid type IncX1, in addition to IncFII(S) and IncFIB(S), is the key carrier of antimicrobial resistance determinants in Salmonella , which is in agreement with previous findings from China and elsewhere ( 54 57 ). Hence, the presence of these plasmids in the studied isolates is of major concern and may mediate the horizontal transmission of antimicrobial resistance along the food chain.…”
Section: Discussionsupporting
confidence: 93%
“…We also validated the serotyping by agglutination assay using SISTR prediction based on genomic sequences. The two methods are highly consistent with a consistency rate of 98%, which is similar to recent reports Uelze et al, 2019;Lyu et al, 2021). However, SISTR has a low identification for Typhimurium and I 4,[5],12:i:-in our research.…”
Section: Discussionsupporting
confidence: 91%
“…This study used traditional and in silico serotyping based on WGS to determine the serotype. Results demonstrated 93.52% concordance between the two methods, close to Cooper et al (2020) (89.2%) and Lyu et al (2021) (96.5%). Several untypable and/or ambiguous serotypes were addressed by in silico serotyping.…”
Section: Discussionmentioning
confidence: 68%